MARKETING STRATEGY OF LAKE TOBA 4 DAYS / 3 NIGHTS TOUR PACKAGE TO KUALA LUMPUR AT PT.NARASINDO TOUR & TRAVEL MEDAN - Padriadi Wiharjokusumo; Dewi Manik (Akademi Pariwisata Darma Agung, 2021)
Marketing strategy is a comprehensive, integrated and unified plan in the field of marketing, which provides guidance on the activities to be carried out in order to achieve the marketing objectives of a company. This research is descriptive qualitative, data obtained from the results of field research, namely the method used to obtain information by conducting interviews directly with relevant sources, such as; the tour manager and marketing staff of PT. Narasindo Tour & Travel Medan and library research which is a method used to obtain information by reading books related to research. From the discussion of the data that has been obtained in the field, the authors conclude that the Marketing Strategy of Lake Toba TourPackage to Kuala Lumpur at PT. Narasindo Tour and Travel Medan, which is participating in tourist exhibitions in Kuala Lumpur, sales visits to Kuala Lumpur, holding table top in Kuala Lumpur, internet or marketing through social media, and having famtrip tours.